2019
DOI: 10.1021/acs.nanolett.8b04339
|View full text |Cite
|
Sign up to set email alerts
|

Zn-Alloyed CsPbI3 Nanocrystals for Highly Efficient Perovskite Light-Emitting Devices

Abstract: We alloyed Zn2+ into CsPbI3 perovskite nanocrystals by partial substitution of Pb2+ with Zn2+, which does not change their crystalline phase. The resulting alloyed CsPb0.64Zn0.36I3 nanocrystals exhibited an improved, close-to-unity photoluminescence quantum yield of 98.5% due to the increased radiative decay rate and the decreased non-radiative decay rate. They also showed an enhanced stability, which correlated with improved effective Goldschmidt tolerance factors, by the incorporation of Zn2+ ions with a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
421
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 421 publications
(453 citation statements)
references
References 59 publications
22
421
1
1
Order By: Relevance
“…Energy level values for CsPbI 3 QD, TCTA, and MoO 3 /Au were taken from ref. Figure 5c shows TEM image of CsPbI 3 QDs, which are monodisperse cubic‐shaped particles with an edge length of 10–12 nm and an interplanar distance of 0.62 nm consistent with the (100) plane of cubic CsPbI 3 . The CBM of ZnO increases from −3.96 to −3.78 eV as a result of the CD 0.33 modification, placing it higher than the lowest unoccupied molecular orbital of CsPbI 3 QDs, offering a barrier to prevent electrons transfer from CsPbI 3 QD emitting layer to ZnO ETL.…”
Section: Resultsmentioning
confidence: 90%
“…Energy level values for CsPbI 3 QD, TCTA, and MoO 3 /Au were taken from ref. Figure 5c shows TEM image of CsPbI 3 QDs, which are monodisperse cubic‐shaped particles with an edge length of 10–12 nm and an interplanar distance of 0.62 nm consistent with the (100) plane of cubic CsPbI 3 . The CBM of ZnO increases from −3.96 to −3.78 eV as a result of the CD 0.33 modification, placing it higher than the lowest unoccupied molecular orbital of CsPbI 3 QDs, offering a barrier to prevent electrons transfer from CsPbI 3 QD emitting layer to ZnO ETL.…”
Section: Resultsmentioning
confidence: 90%
“…Monodisperse CsPbBr 3 nanorods (NRs) were synthesized by hot injection by Yang et al and LEDs were prepared with a structure of ITO/PEDOT:PSS/TFB/CsPbBr 3 NRs/TPBi/LiF/Al, which is one of the best performances of CsPbBr 3 NC‐based LEDs so far (EQE = 8.2%) . Shen and coworkers adopted Zn 2+ doping to synthesize CsPbI 3 NCs and used them as the EML to increase the EQE of red NC LEDs to 15.1% . In addition, blue perovskite NC LEDs have an EQE over 2% …”
Section: Optoelectronic Applications Of Perovskite Ncsmentioning
confidence: 99%
“…216 Shen and coworkers adopted Zn 2+ doping to synthesize CsPbI 3 NCs and used them as the EML to increase the EQE of red NC LEDs to 15.1%. 198 In addition, blue perovskite NC LEDs have an EQE over 2%. 217 Even though the synthetic method of perovskite NCs is becoming more mature, and the perovskite NC LEDs have undergone an impressive development in recent years, there is still a device efficiency gap compared with organic light-emitting diodes (OLEDs) and quantum dot light-emitting diodes (QLEDs).…”
Section: Light-emitting Diodesmentioning
confidence: 99%
“…Further increasing the alloying ratio to 0.49 resulted in a decreased PLQY to 78 %, which was due to the increased defect density or a possible increase in the dark fraction of emitters at higher Zn contents. [65] In a recent work, Li et al employed a post-treatment method of the perovskite NCs employing Zn halide salt/ hexane solution achieved significantly increased PLQY of the CsPbX 3 NCs, boosting the optimum PLQYs to 86, 93, and 95 % for CsPbCl 3 , CsPbBr 3 and CsPbI 3 NCs, respectively. [66] Interestingly, unlike the previous demonstrated Zn 2 + doping, which exhibited obvious blue-shift of the PL emission, no change in the PL emission peaks were observed, which suggested that the post treatment might only affect the surface of the perovskite NCs.…”
Section: Isovalent B-site Doping/alloying Of Perovskite Ncs With Mn 2mentioning
confidence: 99%
“…Reproduced with permission. [65] Copyright © 2019 American Chemical Society. (e) Absorbance and PL spectra of CsPbCl 3 NC with Ni 2 + doping concentration, the inset images are of NC colloidal solution under UV irradiation (f) PL decay of Ni 2 + doped CsPbCl 3 NC.…”
Section: Isovalent B-site Doping/alloying Of Perovskite Ncs Withmentioning
confidence: 99%